2022
DOI: 10.1186/s13046-021-02215-y
|View full text |Cite
|
Sign up to set email alerts
|

The CD70-CD27 axis in oncology: the new kids on the block

Abstract: The immune checkpoint molecule CD70 and its receptor CD27 are aberrantly expressed in many hematological and solid malignancies. Dysregulation of the CD70-CD27 axis within the tumor and its microenvironment is associated with tumor progression and immunosuppression. This is in contrast to physiological conditions, where tightly controlled expression of CD70 and CD27 plays a role in co-stimulation in immune responses. In hematological malignancies, cancer cells co-express CD70 and CD27 promoting stemness, proli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 150 publications
4
66
0
Order By: Relevance
“…In our study, STAT4, CCR7, ARHGAP15, and CD27 were selected as the hub genes to distinguish the different subtypes of PDAC patients. In general, these four genes are all related to the development, maturation, or function of Th1 cells (Oestreich and Weinmann, 2012;Margraf et al, 2020;Salem et al, 2021;Flieswasser et al, 2022). They may affect the prognosis of PDAC patients in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, STAT4, CCR7, ARHGAP15, and CD27 were selected as the hub genes to distinguish the different subtypes of PDAC patients. In general, these four genes are all related to the development, maturation, or function of Th1 cells (Oestreich and Weinmann, 2012;Margraf et al, 2020;Salem et al, 2021;Flieswasser et al, 2022). They may affect the prognosis of PDAC patients in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, treatments targeting CD70 have great potential for treating both early and advanced cancers. However, some studies have shown that CD70 is not up-regulated or not signi cantly up-regulated in tumor cells from Kaposi's sarcoma, prostate cancer, Langerhans cell histiocytosis, and colorectal cancer [14,31]. Although CD70 is prevalent in many cancers, the expression pattern of CD70 varies in terms of spatial distribution, expression intensity, and percentage of positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, developing new immunotherapy targets may be a more effective and promising therapeutic strategy. Thus, the CD70-CD27 axis, which belongs to the tumor necrosis factor (TNF) superfamily, has emerged as an appealing target for tumor development [13,14]. CD70 and CD27 are TNF ligand and receptor family ligand-receptor pairs that are critical for T cell co-stimulation [15].…”
Section: Introductionmentioning
confidence: 99%
“…CD27 is a promising target of immunotherapy. CD27 is a stimulatory immune checkpoint mainly found on the surface of immune cells, which is the receptor of CD70 ( 18 ). Soluble CD27 is a 32kDa cleaved isoform of membrane-bound CD27, which has been reported to interfere interaction of CD27 and CD70 ( 19 ).…”
Section: Discussionmentioning
confidence: 99%